2014
DOI: 10.1016/j.ypmed.2014.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of provider discussion and specific recommendation on colorectal cancer screening uptake among U.S. adults

Abstract: Objectives It is unclear if provider recommendations regarding colorectal cancer (CRC) screening modalities affect patient compliance. We evaluated provider-patient communications about CRC screening with and without a specific screening modality recommendation on patient compliance with screening guidelines. Methods We used the 2007 Health Information National Trends Survey (HINTS) and identified 4,283 respondents who were at least 50 years of age and answered questions about their communication with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 16 publications
4
30
0
Order By: Relevance
“…Incorporating colonoscopy into primary care practices may have the added benefit of ensuring continuity of care, decreasing costs to patients, and decreasing transportation barriers (including travel time). 40 Because a personal physician's recommendation is a strong predictor of CRC screening, [41][42][43][44] and trust in a primary care physician is also associated with CRC screening compliance, 13 primary care colonoscopy has great potential for decreasing CRC incidence and mortality. However, relatively few primary care physicians perform colonoscopies, 23 and only a fraction of family medicine residencies train residents to conduct colonoscopies.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating colonoscopy into primary care practices may have the added benefit of ensuring continuity of care, decreasing costs to patients, and decreasing transportation barriers (including travel time). 40 Because a personal physician's recommendation is a strong predictor of CRC screening, [41][42][43][44] and trust in a primary care physician is also associated with CRC screening compliance, 13 primary care colonoscopy has great potential for decreasing CRC incidence and mortality. However, relatively few primary care physicians perform colonoscopies, 23 and only a fraction of family medicine residencies train residents to conduct colonoscopies.…”
Section: Discussionmentioning
confidence: 99%
“…This was disappointing, since it is known healthcare providers recommendation of CRC screening enhances compliance with screening. [23,24] 4 In previous research, we found that screening rates using FIT were about 48% with a mailed FIT to patients due for screening and a 79% return when handed out to persons in a low-income population. [10,14] Our results are similar to other studies which found about half of the patients return a one-day FIT.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Traditionally, cancer screening is a core component of primary care, and adherence to screening recommendations is a key quality indicator for primary care physicians and practices. Colorectal cancer screening is particularly effective, and expanded screening is credited as contributing to at least some of the declining incidence and mortality from this condition.…”
Section: Introductionmentioning
confidence: 99%